(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The article focuses on the growing use of video and other numerical technologies in staging various theatrical shows, many of them presenting, in their own poetics, feats and resources specific to these new technologies, creating unexpected zones of perception.